Colonoscopic Findings of Patients with Rectal Bleeding: Insights from a Single Centre Study - Elbadry, Mohamed; Tharwat, Mina; Eltaweel, Noha Hamdy; Tahon, Marwa Ali; Mahmoud, Abdelmajeed (Journal of Coloproctology, 2025)
Rectal bleeding is a common symptom prompting an urgent investigation. Colonoscopy plays a crucial role in diagnosing the underlying cause and guiding treatment. We aimed to analyze colonoscopic findings in patients with rectal bleeding at a single center.A retrospective review was conducted on the medical records of patients who underwent colonoscopy for suspected rectal bleeding. Data collected included demographics, clinical presentation, colonoscopic findings, and final diagnoses.A total of 205 patients underwent colonoscopy for rectal bleeding. The mean age was 47.35 ± 14.6 years, with a male predominance of 57.5%. Hematochezia was the most common presentation (73%), followed by melena (18%) and maroon stools (9%). Colonoscopy identified 5 different sources of bleeding. Hemorrhoids were the most common endoscopic finding (76%), followed by combined hemorrhoids and colonic polyps (38%), colonic polyps alone (28%), and colorectal cancer (20%). No lesions were detected in 10% of patients. The left colon emerged as the most frequent site for bleeding lesions (88.1%). Age influenced the distribution of endoscopic findings. Hemorrhoids were prevalent in both age groups, but the presence of both hemorrhoids and polyps/masses was more frequent in younger patients (<45 years). Rectal ulcers were observed exclusively in younger patients, while CRC showed a slightly higher prevalence in this group.Hemorrhoids are the leading cause of LGIB in Upper Egypt, with a higher prevalence compared to other regions. The left colon was the common location for bleeding lesions. Age may influence the causes of LGIB, younger patients present more frequently with combined pathologies.
Keywords: colonoscopy; lower gastrointestinal bleeding; LGIB; hemorrhoids; colon cancer